On the channel usability of Wireless Mesh Networks: when stability plays with you. (29th July 2011) - Yang, Panlong; Qin, Guangcheng; Yan, Yubo; Wang, Hai; Zhang, Lei; Chen, Guihai; Guo, Deke
In this work, we are striving for a perfect balance on utilisation between reliable channels and unreliable channels, where the network throughput can be maximised. We propose 'p-stable', a distributed Multi-phase Maximum Weighted Matching algorithm. We also apply channel bundles to effectively improve stability in the network, and prove the problem NP-hard. The time complexity is O(Δ³ + (log. * n)²), and overhead complexity is O(Δ × (Δ + n) + n α + log n), with Δ denoting maximum number of node degree in an n nodes network. Simulation results show that p-stable design effectively improves network stability, especially upon the existence of large number of unreliable channels.